Cetuximab versus bevacizumab maintenance following prior 8-cycle modified FOLFOXIRI plus cetuximab in Asian postmenopausal women with treatment-naive KRAS and BRAF wild-type metastatic colorectal cancer. Issue 9 (September 2020) - Chen, Baomin; Zheng, Donghua; Yu, Weiguang; Huang, Cuiping; Ye, Junxing; Han, Guowei; Zhuang, Jintao
Objective: To assess the efficacy and safety of cetuximab (CE) versus bevacizumab (BE) maintenance treatment after prior 8-cycle modified 5-fluorouracil, folinate, oxaliplatin, and irinotecan (FOLFOXIRI) plus CE induction therapy in treatment-naive KRAS and BRAF wild-type (wt) metastatic colorectal cancer (mCRC). Methods: From 2012 to 2017, prospectively maintained databases were reviewed to assess Asian postmenopausal women with treatment-naive KRAS and BRAF wt mCRC who underwent modified FOLFOXIRI plus CE induction therapy, followed by CE or BE maintenance until disease progression or death. Co-primary clinical endpoints were progression-free survival (PFS) and overall survival (OS). Results: A total of 222 women were included (CE n = 110 and BE n = 112). At a median follow-up of 27.0 months (interquartile range, 6.5–38.6 months), median PFS was 21.9 months (95% confidence interval [CI] 16.4–24.4) and 17.7 months (95% CI 11.3–19.0) for CE and BE groups, respectively (hazard ratio [HR] 0.31, 95% CI 0.15–0.46); median OS was 26.0 months (95% CI 23.4–28.7) and 22.7 months (95% CI 21.2–24.3) for CE and BE groups, respectively (HR 0.22, 95% CI 0.11–0.37). Conclusions: CE maintenance treatment is more poorly tolerated but has a slightly more modest survival benefit compared with BE maintenance treatment in mCRC.